2016
DOI: 10.1016/j.ultras.2015.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Inverse characterization of plates using zero group velocity Lamb modes

Abstract: In the presented work, the characterization of plates using zero group velocity Lamb modes is discussed. First, analytical expressions are shown for the determination of the k-ω location of the zero group velocity Lamb modes as a function of the Poisson's ratio. The analytical expressions are solved numerically and an inverse problem is formulated to determine the unknown wave velocities in plates of known thickness. The analysis is applied to determine the elastic properties of tungsten and aluminum plates ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…At these zero group velocity (ZGV) frequencies, sharp and local resonance effects are observed. The sensitivity of the ZGV modes has been exploited for precise local plate thickness measurements 35 , for absolute and local measurements of the Poisson's ratio of several isotropic media 36,37 , or to highlight the anisotropic constitutive behaviour of bulk silicon 38 . Recent studies also reported on the mechanical characterisation of complex nanoscale structures such as lowdensity nanoporous gold foams 39 or nanoscale bilayers consisting of a silicon-nitride plate coated with a titanium film 40 .…”
mentioning
confidence: 99%
“…At these zero group velocity (ZGV) frequencies, sharp and local resonance effects are observed. The sensitivity of the ZGV modes has been exploited for precise local plate thickness measurements 35 , for absolute and local measurements of the Poisson's ratio of several isotropic media 36,37 , or to highlight the anisotropic constitutive behaviour of bulk silicon 38 . Recent studies also reported on the mechanical characterisation of complex nanoscale structures such as lowdensity nanoporous gold foams 39 or nanoscale bilayers consisting of a silicon-nitride plate coated with a titanium film 40 .…”
mentioning
confidence: 99%
“…Also, an interesting feature shows up at 102 Hz where the branches A1 and A * 2 nearly meet each other. In a nondissipative system, one expects the two branches to connect, thus yielding a singular point associated with a ZGV, a phenomenon which has been previously observed in rigid plates (37)(38)(39)(40)(41). Here, because the propagation is damped by viscous mechanisms, the connection does not strictly occur, the reason why we talk about the pseudo-ZGV mode, but as we will see below similar wave phenomena still exist in the presence of damping (see SI Appendix, Fig.…”
Section: Significancementioning
confidence: 67%
“…At these zero group velocity (ZGV) frequencies, sharp and local resonance effects are observed. The sensitivity of the ZGV modes has been exploited for precise local plate thickness measurements [32], for absolute and local measurements of the Poisson's ratio of several isotropic media [33,34], or to highlight the anisotropic constitutive behaviour of bulk silicon [35]. Recent studies also reported on the mechanical characterization of complex nanoscale structures such as low density nanoporous gold foams [36] or nanoscale bilayers consisting of a silicon-nitride plate coated with a titanium film [37].…”
Section: Introductionmentioning
confidence: 99%